Transition metal attenuated mechanism for protective alumina formation from first principles. Issue 72 (11th December 2018) - Babic, Vedad; Geers, Christine; Panas, Itai
Abstract : A mechanistic perspective on the growth of protective oxides on high temperature alloys at elevated temperatures is provided. Abstract : A mechanistic perspective on the growth of protective oxides on high temperature alloys at elevated temperatures is provided. Early, defect rich transient alumina is understood to form by outwards diffusion of oxygen vacancies and electrons. The impact of transition metal (TM) ions (Sc, Ti,  V, Cr, Mn, Fe, Co, Ni) on the oxygen vacancy diffusion and electron transport in α-alumina was studied by employing density functional theory. Activation energies for electron transfer E A (ET) between oxygen vacancies in pure as well as TM doped α-alumina were subject to analysis, and similarly so for the TM and charge dependent activation energy for oxygen vacancy diffusion E A ( V O ). E A Q (ET) were found to be ∼0.5 eV while 2 eV < E A Q ( V O ) < 5 eV was obtained. The higher and lower E A Q ( V O ) values correspond to uncharged and doubly charged V O sites, respectively. Redox processes among V O sites, addressed by a bipolaron approach, were understood to enhance V O mobility and thus to facilitate oxide growth. TM adatoms induced asymmetry in the potential energy surface for oxygen vacancy diffusion was subject to analysis. Competition for electrons between all-Al 3+ surrounded oxygen vacancies and vacancies adjacent to the late 3d adatoms comes out in favor of the latter. A novel take on the 3rd element effect in FeCrAl emerges from analysis of the ternary TM–TM*–Al system.